Caecal duplication cyst mimicking intussusception - Verma, Shraddha (BMJ Publishing Group, 2013)
Cystic caecal duplication is a rare congenital anomaly. We report a case of an infant, who presented with bilious vomiting and abdominal distension. On ultrasonography, intussusception with a cyst as a lead point was present in the right iliac fossa. On exploration, there was no evidence of intussusception, only caecal duplication cyst was found. To date, only three cases of caecal duplication which mimicked intussusception have been reported in the English literature.